2013
DOI: 10.1111/acer.12114
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between an Abusive Father-Son Relationship, Quantity of Alcohol Consumption, and Male-to-Male Alcohol-Related Aggression

Abstract: Negative father-son relationships may play a role in fostering young men's perpetration of MMARA in the barroom context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…Men were more likely to be involved in both verbal and physical aggression; although odds were higher for physical aggression. This accords with previous research and reflects the reality that males are affected by a range of developmental, biological, psychological, social and societal influences, which predispose them to experience higher levels of violence throughout their lifetime . In contrast, women from the POINTED study were more likely to report involvement in an alcohol‐related accident or injury in the past 3 months .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Men were more likely to be involved in both verbal and physical aggression; although odds were higher for physical aggression. This accords with previous research and reflects the reality that males are affected by a range of developmental, biological, psychological, social and societal influences, which predispose them to experience higher levels of violence throughout their lifetime . In contrast, women from the POINTED study were more likely to report involvement in an alcohol‐related accident or injury in the past 3 months .…”
Section: Discussionsupporting
confidence: 87%
“…While the reasons for these findings have not been well explored, those living in the most socio‐economically disadvantaged areas are more than twice as likely to report experiencing ARA compared with those living in the most advantaged areas . Drivers, such as drinking norms or lifetime exposure to violence may play a role though further research is required.…”
Section: Discussionmentioning
confidence: 99%
“…While some have suggested that conformity to 'masculine norms' may be related to aggression and risky drinking, Australian research has demonstrated that when trait aggression is investigated with masculinity, it is a much stronger predictor. It has also been found that young men are more likely to experience physical aggression in childhood than adulthood, and that this experience is a strong predictor of antisocial behaviour and heavy drinking [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Choice of items to represent each construct was based on principal components analyses with varimax rotation, conducted on data previously collected by the research team using the full measures with Australian samples (e.g. ).…”
Section: Methodsmentioning
confidence: 99%